The construction of expert knowledge on toxic colours and responses to industrial hazards in France and Britain (1814-1914) - Bonney, A (2024)
This thesis examines how changing approaches to the study of toxicity shaped responses to the industrial and occupational hazards of colour production and use in France and Britain between 1814 and 1914. During this period, investigations conducted by toxicologists, chemists, pharmacists, medical practitioners and veterinarians motivated conflicting discourses on the risks posed by toxic elements used for colour production such as lead, arsenic, copper, aniline, or picric acid. Tensions arose due to disagreements over scientific methodologies of investigation, conflicting conceptions of state intervention and disease, and the unstable nature of nomenclatures used to classify colour, disease, and industrial nuisances. Despite structural differences in terms of educative systems, legal frameworks and access to resources used for colour production, environmental and occupational risks of colour production thus became rationalised and naturalised in both France and Britain. Examining the rise of synthetic colour production through the lens of environmental history therefore challenges narratives according to which the age of synthetic colours marked a ‘colour revolution’. Instead, it consolidated risk management regimes which pre-dated the production of synthetic colours.